The acute mechanism of the self-massage-induced effects of using a foam roller. (July 2021) - Yoshimura, Akane; Sekine, Yuta; Schleip, Robert; Furusyo, Atsuya; Yamazaki, Kazuya; Inami, Takayuki; Murayama, Mitsuyoshi; Hirose, Norikazu
Abstract: Introduction: Maintaining flexibility, often defined as range of motion (ROM), is important. Recently, self-massage using a foam roller (FR) has been used in clinical and/or sports settings to effectively and immediately improve ROM. Many studies have found significant increases in ROM following the FR intervention; however, the mechanism of the effect is unclear. We aimed to clarify this mechanism regarding the ROM effects following the FR intervention by evaluating local tissue and autonomic nervous system responses. Method: The study employed a crossover design that included a comparison between non-intervention (CON trial: left leg) and intervention (FR trial: right leg) groups. Fourteen volunteers participated. Nine outcomes (passive maximum ankle ROM [ROM with a specified and non-specified passive strength], tissue hardness, skin temperature, water contents, circumference, blood flow velocity, pressure pain threshold, autonomic nervous system, and heart rate) were investigated before (PRE) and 0 min (POST0), 20 min (POST20), 40 min (POST40), and 60 min (POST60) post intervention. Results: Skin temperature, impedance, and circumference changed significantly following the intervention, and increased ROM with non-specified strength was observed. Discussion: Although we found that the FR intervention influenced skin temperature, impedance, circumference, and ROM, adaptability to the intervention may differ depending on an individual's characteristics. Females and/or individuals with a high body water content could obtain greater positive ROM effects than males and/or individuals with a low body water content. Conclusion: These findings suggest that the FR intervention may be an effective method to improve ROM, with alterations of skin temperature, impedance, and circumference.